Biodeterioration of the Nik An (Tschudi) palace, Chan Chan Archaeological Complex, Trujillo, La Libertad, Peru: Flora - Rodríguez Rodríguez, Eric F.; Herbarium Truxillense (HUT), Universidad Nacional de Trujillo (2021)
The Archaeological Complex of Chan Chan is made up of various pre-Hispanic structures whose monumental architecture has clay as its raw material; one of them is the Nik An (Tschudi) palace. The study was carried out between 2014 and 2017; it was based on botanical collection and direct field observations of both flora and deterioration. Twelve species distributed in 11 families and 12 genera were recorded, of them 2 cryptogams (2 lichen species) and 10 phanerogams (5 herbs, 1 suffrutice, 1 subshrub, 2 shrubs and 1 tree). The taxa are found inside the architectural complex at the base, on the walls, roads and passageways, causing two types of effects on the substrate: biogeophysical (mechanical) and biogeochemical; as well as potential biodeterioration agents.